Metastatic renal cell carcinoma - a case report - Grzegorz Wróbel (Kazimierz Wielki University, 2017)
Renal cell carcinoma (RCC) is not a single uniform entity but a group of related neoplasms in which the histologic findings, cytogenetic abnormalities, biologic behavior and imaging appearances of the tumors are subtype dependent. PET-CT is the fusion of functional and anatomic information acquired almost simultaneously that lets us see the body and disease in a way that is diagnostically very powerful. The case concerns the result imaging 18F-fluorodeoxyglucose positron emission tomography (PET)-CT to patient 47 years old (women) is diagnosed with numerous changes in both lungs, the liver and the skeletal system in the abdominal lymph nodes. Primary change in left kidney is indicated. Metastasis is a process consisting of cells spreading from the primary site of the cancer to distant parts of the body. Functional imaging, particularly with PET-CT, might improve the accuracy of diagnosis and provide essential information that could allow clinicians to make more appropriate therapeutic decisions than they previously could without this technique.